(untitled) (Research in Agriculture Livestock and Fisheries, 2015)
The present study was conducted to estimate the garlic feed supplement on hematobiochemical parameters in lead exposed broiler chickens. 350 commercial broiler chickens were grouped into five, as T0, T1, T2, T3 and T4 consisting of 70 birds each, where T0 served as control. T1 was provided with lead acetate @ 100mg/kg body weight, T2 @ 100mg/kg lead acetate + 1% garlic supplement, T3 was fed @ 100mg/kg lead acetate + 2% garlic supplement and T4 @ 100mg/kg lead acetate + 4% garlic supplement .It was observed that Garlic supplementation in feed has got some ability to maintain normal values of erythrocytes, leukocytes, ALT, AST & Cholesterol parameters in spite of treatment with lead acetate. It was also found highly significant (P<0.001) in 2% garlic supplemented group (T3) compared to that of 1% (T2) and 4% (T4) garlic supplemented groups. The mean values of erythrocyte, Hb. and PCV significantly reduced from 2.217±0.020 to 2.062±0.047, 7.697±0.247 to 6.172±0.198 and 25.183±0.8122 to 23.532±1.001, respectively in group T1. The ameliorating effects of garlic in heavy metal lead revealed significantly (P<0.01) increased erythrocyte, hemoglobin and PCV values from 2.16±0.034 to 2.46±0.077, 8.362±0.262 to 10.44±0.26 and 23.64±0.90 to 30.68±0.75 in group T3, respectively. The mean values of ALT, AST and Cholesterol with lead Acetate @ 100mg/kg treatment were significantly (P<0.01) increased from 30.11±1.135 to 36.274±1.192, 51.162±1.422 to 103.641±2.023 and 152.34±17.47 to 364.28±12.33, respectively in T1 group on 42nd Day of treatment. The calculated significant mean values (mg/dl) of ALT, AST and Cholesterol were 24.51±0.63, 57.95±1.68 and 203.62±12.76, respectively in T3 group. The protection action of garlic against lead toxicity could be attributed to the antioxidant action of its sulfhydryl groups. DOI: http://dx.doi.org/10.3329/ralf.v1i1.22364 Res. Agric., Livest. Fish.1(1): 87-96, Dec 2014